2001
DOI: 10.1007/s10434-001-0833-7
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Internal Mammary Lymph Node Removal When Noted by Intraoperative Gamma Probe Detection

Abstract: Radioguided SLN detection should be attempted in the IMN basin with all tumors. If an IMN is identified, it should be removed. IMN biopsy is a feasible, low-risk procedure when directed by radioguided LM and provides a guide for radiotherapy for patients with positive IMNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…11 Other surgeons are following suit, and the current study may increase their awareness of where to expect sentinel nodes. [12][13][14][15][16] …”
Section: Discussionmentioning
confidence: 98%
“…11 Other surgeons are following suit, and the current study may increase their awareness of where to expect sentinel nodes. [12][13][14][15][16] …”
Section: Discussionmentioning
confidence: 98%
“…4,5 In addition, the presence of IMC metastases depends on tumor location in the breast, with a higher prevalence of IMC metastases in tumors of the inner quadrants, especially the lower-inner quadrant. [6][7][8] The IMC is not routinely investigated for the presence of lymph node metastases, and breast cancer is classified as lymph node negative on the basis of axillary lymph node investigations only. Undetected IMC metastases, therefore, lead to under-staging of patients without axillary lymph node involvement and to under-treatment of stage I patients who have no indication of adjuvant chemotherapy.…”
mentioning
confidence: 99%
“…With recent studies citing the low morbidity associated with extra-axillary, specifically internal mammary, sentinel lymph node biopsy, the question of whether extra-axillary SLNB should be performed has been raised by many authors. 34-36 Veronesi and others have shown that IM lymph node involvement confers a poorer prognosis and shorter survival. 37 The 2006 revisions to the American Joint Committee on Cancer staging manual reflect the importance of IM nodes in breast cancer staging.…”
Section: Discussionmentioning
confidence: 99%